Evaluation of intracapsular total thyroidectomy as a safe method in benign thyroid diseases - Elgamaal, Ahmed S.; Fayed, Asem; Elbalshy, Mohammed A.; Aziz, Mohamed M. (International Surgery Journal, 2019)
Background: Intracapsular total thyroidectomy is a rising new technique in management of benign thyroid disease seeking for safety. Our aim in this study is to evaluate safety and effectiveness of intracapsular technique in treatment of benign thyroid disease. Methods: this prospective study was carried out in department of general surgery, Menoufia University hospital and department of general surgery, Tala central hospital; from June 2018 to April 2019 on 58 patients with benign thyroid disease all had undergone intracapsular total thyroidectomy. Results: 58 patients underwent intracapsular total thyroidectomy. There was no recurrent laryngeal nerve injury either transient or permanent and no external laryngeal nerve injury. There was no parathyroid injury or hypoparathyriod complications. Conclusions: Intracapsular total thyroidectomy is a safe method in treatment of benign thyroid disease and can be done easily in central hospitals and non-highly specialized centres.